Broader-Based and Sectoral Bargaining in Collective-Bargaining Law Reform: A Historical Review - Slinn, Sara J. (Labour / Le Travail)

(untitled) (Canadian Committee on Labour History, 2020)
Compelling evidence exists that centralized bargaining structures, including broader-based and sectoral bargaining (bbb), offer significant benefits to workers. Examining the role of bbb in major Canadian labour law reform initiatives between the late 1980s and 2019, this article explores why the labour movement, despite the potential advantages of bbb, has not collectively pursued bbb reforms. It concludes with an analysis of the failure to incorporate bbb proposals into labour legislation and an assessment of the key challenges to adopting significant bbb reforms in the future. Earlier research concluded that bbb proposals in the 1990s failed because of employer opposition and lack of understanding, including by labour. This study departs from earlier conclusions to find that neither of these factors has been prominent regarding bbb in recent decades. Instead, lack of support for bbb arises from some unions’ concerns about preserving existing representation rights, resistance to the prospect of mandatory councils of unions, and anticipation of jurisdictional conflicts. Lack of support for bbb from some peak labour organizations arises from a consensus approach to deciding which labour law reform issues to promote. An additional challenge to its adoption is the politicized nature of labour law reform, and the political cost of innovative and untried proposals deter governments from adopting bbb.